ADJUNCTIVE VITAMIN D IN ALLERGIC RHINITIS: A RANDOMIZED CONTROLLED STUDY - Dr. Kirti Agrawal; Amit Modwal (EPH-International Journal of Medical and Health Science, 2026)
Allergic rhinitis (AR) is a very common chronic inflammatory condition of the nasal mucosa, which has a negative impact on life, sleep and productivity. The immunomodulatory effects of vitamin D (Vit D) have been well established and its effects on allergic inflammation are likely but the effects of Vit D as an adjunctive therapy for AR is still being studied. We conducted a randomized controlled trial to assess the effectiveness of Vit D supplementation, in addition to intranasal corticosteroid therapy, in Vit D deficient patients with allergic rhinitis. A total of 300 patients were evaluated and 110 who had 20-29 ng/mL of serum 25-hydroxyVit D were randomly divided into two groups of 55 patients. Fluticasone alone was given to Group A and fluticasone in combination with Vit D to Group B. Total Nasal Symptom Score (TNSS) was evaluated at baseline, 4 weeks and 8 weeks, and the serum Vit D was measured. 80% of screened patients were found to have hypovitaminosis D. The TNSS gradually decreased in both groups, but Group B showed more improvement from 8.15 at baseline to 4.90 at 4 weeks and 2.77 at 8 weeks, while Group A went from 8.35 at baseline to 6.80 at 4 weeks and 5.24 at 8 weeks. There was a significant difference between the two groups in the post-treatment (p < 0.0001). Vit D could thus be an adjunctive medication providing extra symptomatic relief in Vit D deficient allergic rhinitis patients.